ANALISIS EVALUASI TINGKAT LITERASI KEAMANAN CYBER PENGGUNAAN MEDIA SOSIAL (STUDI KASUS SISWA SMK BUKIT ASAM) - Ikhwan Amalsyah; M. Rudi Sanjaya; Endang Lestari Ruskan; Dwi Rosa Indah (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
This study aims to analyze the level of cyber security literacy among students of SMK Bukit Asam and classify it using the Random Forest algorithm. A quantitative approach was employed with a questionnaire covering four key indicators: knowledge, attitude, behavior, and overall cyber security literacy. A total of 192 students participated as respondents. The results show that 53.13% of students fall into the high literacy category, 35.94% into the medium category, and 10.94% into the low category. The Random Forest model achieved an accuracy of 97.44%, with SI2 and SI4 identified as the most influential features. Beyond describing the students’ generally good level of cyber security literacy, the use of Random Forest also provides an important methodological contribution by revealing attitude-related indicators as the main determining factors in the classification. These findings offer a clearer foundation for designing more targeted and effective digital security education programs in schools.